Exploring the relationship between physical activity knowledge, health outcomes expectancies, and behavior - Heinrich, Katie M.; Maddock, Jay E.; Bauman, Adrian (My University, 2012)
Background: Despite clear health benefits of physical activity, previous research has been limited in linking knowledge of physical activity recommendations to actual behavior. Methods: Using Expectancy Theory, we examined whether an individual’s health outcome expectancies from physical activity might provide the missing link between knowledge and behavior. With data from a cross-sectional survey, we assessed differences between how much moderate physical activity people thought they needed for health benefits compared with what they thought experts recommended and the relationship of these differences to physical activity behaviors. Results: Our hypothesis that people with positive health outcome expectancies would report more minutes of physical activity than those with neutral or negative health outcome expectancies was supported for all self-reported physical activity behaviors (P < .001). Conclusions: It appears that the health outcome expectancy of needing more physical activity than recommended by experts is correlated with achieving more physical activity, regardless of type. Future research should address health outcome expectancies as a way to impact physical activity.
Keywords: Walking; Survey; Adults; Moderate; Vigorous